2003
DOI: 10.1073/pnas.0437870100
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide hydroxamic acid, a histone deacetylase inhibitor, ameliorates motor deficits in a mouse model of Huntington's disease

Abstract: Huntington's disease (HD) is an inherited, progressive neurological disorder that is caused by a CAG͞polyglutamine repeat expansion and for which there is no effective therapy. Recent evidence indicates that transcriptional dysregulation may contribute to the molecular pathogenesis of this disease. Supporting this view, administration of histone deacetylase (HDAC) inhibitors has been shown to rescue lethality and photoreceptor neurodegeneration in a Drosophila model of polyglutamine disease. To further explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
522
2
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 787 publications
(565 citation statements)
references
References 29 publications
34
522
2
7
Order By: Relevance
“…Accordingly, we do not believe that the absence of a definite effect on lifespan reduces the potential therapeutic value of rapamycin or CCI-779. Other researchers also do not use lifespan as an indicator in therapeutic trials in mice, which they euthanize at humane end points 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we do not believe that the absence of a definite effect on lifespan reduces the potential therapeutic value of rapamycin or CCI-779. Other researchers also do not use lifespan as an indicator in therapeutic trials in mice, which they euthanize at humane end points 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo studies have shown that treatment with HDAC inhibitors of a wide range of structures provide neuroprotective effects in models of various motor neuron disorders. [44][45][46][47] However, the roles of glia under therapeutic mechanisms of HDAC inhibitors were not investigated. Here we showed that the neurotrophic effects of VPA, a HDAC inhibitor of short-chain fatty acid structure, were associated with Figure 5 VPA is neuroprotective against LPS-induced DA neurodegeneration in rat primary mesencephalic neuronglia cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, valproate and several other HDAC inhibitors have shown neuroprotective effects in animal models of cerebral ischemia, 190,191 Parkinson's disease, 192 and Huntington's disease. 193,194 Weaver and associates 195 demonstrated in rat pups that behaviorally programmed, persistent epigenomic alterations of a glucocorticoid receptor gene promoter in the hippocampus induced by certain styles of maternal behavior could be reversed by central infusion of an HDAC inhibitor. Tremolizzo and colleagues 196 found that hypermethylation of the reelin promoter and subsequent decrease of reelin expression, which have been suggested by recent studies to be present in BD and schizophrenia patients, were prevented by valproate in doses inhibitory to HDACs.…”
Section: Valproate Histone Deacetylase and Epigenetic Regulation Ofmentioning
confidence: 99%